Inorganic phosphorus fractions and crop productivity in response to different rates of phosphate-solubilising fungi Penicillium bilaii - SINGH, Y V; GAIND, SUNITA (The Indian Journal of Agricultural Sciences, 2019)
Two field experiments were conducted at experimental farm of ICAR-Indian Agricultural Research Institute, New Delhi during 2014-15 to investigate the interactive effect of three rates of seed inoculation with wettable formulation of phosphate solubilising fungi (Penicillium bilaii) and two rates (60 kg and 30 kg P2O5/ha) of chemical phosphorus (P) fertilization on soil P availability and productivity in wheat (Triticum aestivum L.) and mustard (Brassica campestris L.) crops. Inorganic P distribution in different fractions was conducted by successive extraction of soil P with water, NaHCO3 (SB-P), NaOH (SH-P) and HCl. Application of fungal formulation @10.604 g/kg mustard seed and 4.894 g/kg wheat seed + 30 kg P2O5/ha as chemical P increased the SB-P fraction of mustard and wheat grown soil by 145.7% and 140.7%, respectively compared to their respective un-inoculated controls at maturity. HCl-P was the major fraction under wheat soil with average contribution of 46% and 64.8% of total extractable P at 60 and 120 d of crop growth whereas SH-P was the major fraction under mustard grown soil. Improved soil P availability due to fungal inoculation could explain the role of phosphate solubilising fungi in soil P mobilization. The crop productivity however, was highest with highest rate of chemical P and fungal based formulation.